I‐IFTA and chronic active T cell–mediated rejection: A tale of 2 (DeKAF) cohorts. Issue 5 (8th November 2020) - Helgeson, Erika S.; Mannon, Roslyn; Grande, Joseph; Gaston, Robert S.; Cecka, Michael J.; Kasiske, Bertram L.; Rush, David; Gourishankar, Sita; Cosio, Fernando; Hunsicker, Lawrence; Connett, John; Matas, Arthur J.
Abstract : Inflammation in areas of fibrosis (i‐IFTA) in posttransplant biopsies is part of the diagnostic criteria for chronic active TCMR (CA TCMR ‐‐ i‐IFTA ≥ 2, ti ≥ 2, t ≥ 2). We evaluated i‐IFTA and CA TCMR in the DeKAF indication biopsy cohorts: prospective (n = 585, mean time to biopsy = 1.7 years); cross‐sectional (n = 458, mean time to biopsy = 7.8 years). Grouped by i‐IFTA scores, the 3‐year postbiopsy DC‐GS is similar across cohorts. Although a previous acute rejection episode (AR) was more common in those with i‐IFTA on biopsy, the majority of those with i‐IFTA had not had previous AR. There was no association between type of previous AR (AMR, TCMR) and presence of i‐IFTA. In both cohorts, i‐IFTA was associated with markers of both cellular (increased Banff i, t, ti) and humoral (increased g, ptc, C4d, DSA) activity. Biopsies with i‐IFTA = 1 and i‐IFTA ≥ 2 with concurrent t ≥ 2 and ti ≥ 2 had similar DC‐GS. These results suggest that (a) i‐IFTA≥1 should be considered a threshold for diagnoses incorporating i‐IFTA, ti, and t; (b) given that i‐IFTA ≥ 2, t ≥ 2, ti ≥ 2 can occur in the absence of preceding TCMR and that the component histologic scores (i‐IFTA, t, ti) each indicate an acute change (albeit i‐IFTA on the nonspecific background of IFTA), the diagnostic category "CA TCMR" should be reconsidered. Abstract : This study of two indication‐biopsy cohorts questions the Banff diagnostic category of chronic active T cell–mediated rejection. Naesens et al. comment on page 1689 .